Plantio direto de milho e integração lavoura-pecuária - Edmar Eduardo Bassan Mendes; Roberto Molinari Peres; Aildson Pereira Duarte; Célio Luiz Justo; Denyse Chabaribery; José Luiz Viana Coutinho Filho (Boletim de Indústria Animal, 2013)
O artigo não apresenta resumo em português.